Association of sleep quality and quality of life in type 2 diabetes mellitus: A cross-sectional study in China - Lou, Peian; Qin, Yu; Zhang, Pan; Chen, Peipei; Zhang, Lei; Chang, Guiqiu; Li, Ting; Qiao, Cheng; Zhang, Ning (Diabetes research and clinical practice, 2015)
The aim of this study is to investigate sleep quality and quality of life, and to assess the relationship between sleep quality and quality of life in Chinese patients with type 2 diabetes mellitus (T2DM). 944 patients with T2DM were enrolled in our study. General characteristics and laboratory testing such as glycosylated hemoglobin A1c (HbA1c) were measured. Each patient completed a Chinese version of the Pittsburgh sleep quality index (PSQI) and the diabetes specificity quality of life scale (DSQL) questionnaires. A PSQI global score >7 was defined as poor sleep quality. A global DSQL score <40 was defined as a good quality of life. Multiple logistic regression analysis was used to examine the relationships between PSQI and DSQL. Poor quality of life in participants was associated with a longer duration of diabetes, a greater number of diabetes complications, no alcohol drinking, poor glycemic control and having depression and anxiety (all P<0.001). Of the participants, 33.6% of them were poor sleepers according to their PSQI. Poor sleepers had significantly lower DSQL (P<001). After adjustment for confounders, poor sleep quality was positively associated with a lower health-related quality of life (OR: 3.67, 95% CI: 1.30–10.33, P<0.001). Our results suggest that poor sleep is prevalent in T2DM and inversely associated with quality of life. It is necessary for primary health-care workers to include sleep related knowledge in diabetes self-management programs to improve sleep quality in diabetes patients.